(untitled) ("Conference on Universal Science Research 2023", 2023)
Coronavirus infection (COVID-19), according to world literature and experience, caused a pandemic, which not only led to a revision of approaches to the diagnosis and treatment of infectious diseases, but also required a reassessment of the role of radiodiagnosis methods in detecting COVID-19 and its complications, evaluating the effectiveness of ongoing treatment and verification of manifestations of post-covid syndrome. Of course, in the primary diagnosis of the disease, special attention is paid to the state of the lungs, while more and more data indicate the involvement of the organs of the gastrointestinal tract and other target organs in the process. Obviously, it is computed tomography (CT) that forms the basis of radiation diagnostics of COVID-19 [1,3,6].